Mutations in the TGF-β Repressor SKI Cause Shprintzen-Goldberg Syndrome with Aortic Aneurysm - Doyle, Alexander J. (2012)
Increased transforming growth factor beta (TGF-β) signaling has been implicated in the pathogenesis of syndromic presentations of aortic aneurysm, including Marfan syndrome (MFS) and Loeys-Dietz syndrome (LDS)(1-4). However, the location and character of many of the causal mutations in LDS would intuitively infer diminished TGF-β signaling(5). Taken together, these data have engendered controversy regarding the specific role of TGF-β in disease pathogenesis. Shprintzen-Goldberg syndrome (SGS) has considerable phenotypic overlap with MFS and LDS, including aortic aneurysm(6-8). We identified causative variation in 10 patients with SGS in the proto-oncogene SKI, a known repressor of TGF-β activity(9,10). Cultured patient dermal fibroblasts showed enhanced activation of TGF-β signaling cascades and increased expression of TGF-β responsive genes. Morpholino-induced silencing of SKI paralogs in zebrafish recapitulated abnormalities seen in SGS patients. These data support the conclusion that increased TGF-β signaling is the mechanism underlying SGS and contributes to multiple syndromic presentations of aortic aneurysm.